Evaluation of Soil Pedological Variability and Carbon Stock in Major Coconut-supporting Soils of the South Deccan Plateau Region, India - R. Srinivasan; M. Lalitha; B. Kalaiselvi; N. Maddileti; S. Parvathy; M.S. Laalithya; Jagdish Prasad; V. Ramamurthy (Journal of the Indian Society of Soil Science, 2025)
Coconut a major plantation crop is cultivated in different pedo-edaphic environments of Southern India. The coconut-supporting soils of the South Deccan plateau having their genesis on granite-gneiss were surveyed (1:10000 scale) and characterized. Six soil series (tentative), namely Chikkonahalli (CKH), Kattigehalli (KGH), Baddikare (BDK), Maradihalli (MDH), K. Hosuru (KHU), and Hebbalalu (HBL) were identified. The soils of these series were shallow (150 cm), well to moderately drained, reddish-brown to brown in colour, and gravelly (15 to 85%). Their texture varied from loamy sand to clay with sub-angular blocky to crumb in structure. These soils were neutral to moderately alkaline, nonsaline, and had low to high organic carbon (0.49 to 0.85%) but low to medium in CEC (5.10 to 20.38 cmol[p+]kg-1). The exchange complex was dominated by calcium followed by magnesium, potassium, and sodium. The organic carbon stock in these soils varied from 4.16 to 59.80 t C ha-1, 32.66 tC ha-1 in Fluventic Haplustepts, and 30.19 t C ha-1 in Kanhaplic Rhodustalfs. Understanding the potential, constraints and soil organic carbon stock of coconut-supporting soils could help in identify the best management practices for sustainable productivity.